2020
DOI: 10.1097/aog.0000000000003702
|View full text |Cite
|
Sign up to set email alerts
|

Occult Tubal Carcinoma After Risk-Reducing Salpingo-oophorectomy

Abstract: OBJECTIVE: To perform a systematic review of the literature to estimate the prevalence and outcomes of occult tubal carcinoma in BRCA mutation carriers and high-risk patients undergoing risk-reducing salpingo-oophorectomy. DATA SOURCE: A search was done using OVID MEDLINE, EMBASE, and ClinicalTrials.gov between 1946 and March 2019 with keywords and MeSH terms selected by an expert medical librarian and coauthors. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In literature, the occult ovarian/tubal cancer rate in BRCA1/2 mutation carriers undergoing RRSO has been reported to be 0.6%–17%. 15 16 17 18 19 Therefore, it is recommended that BRCA1/2 mutation carriers, especially those who completed childbearing, undergo RRSO soon after genetic testing to prevent the development of ovarian/tubal cancer and microscopic cancer progression. Nevertheless, neglecting cancer screening after RRSO should be avoided, as the risks of developing primary peritoneal cancer and breast cancer still remain.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, the occult ovarian/tubal cancer rate in BRCA1/2 mutation carriers undergoing RRSO has been reported to be 0.6%–17%. 15 16 17 18 19 Therefore, it is recommended that BRCA1/2 mutation carriers, especially those who completed childbearing, undergo RRSO soon after genetic testing to prevent the development of ovarian/tubal cancer and microscopic cancer progression. Nevertheless, neglecting cancer screening after RRSO should be avoided, as the risks of developing primary peritoneal cancer and breast cancer still remain.…”
Section: Discussionmentioning
confidence: 99%
“…Much of this evidence is based on the discovery of occult carcinoma and pre-cancerous lesions in the fallopian tube at the time of RRBSO. A systematic review of 24 studies including a total of 6283 patients (4473 BRCA1/2 carriers) found 75 patients with occult tubal carcinoma at time of RRBSO in addition to 93 patients with STIC/STIL ( Piedimonte et al, 2020 ). Table 1 (adapted from Piedimonte et al (2020) ) details the histologic findings and location of occult carcinomas from studies included in the systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 24 studies including a total of 6283 patients (4473 BRCA1/2 carriers) found 75 patients with occult tubal carcinoma at time of RRBSO in addition to 93 patients with STIC/STIL ( Piedimonte et al, 2020 ). Table 1 (adapted from Piedimonte et al (2020) ) details the histologic findings and location of occult carcinomas from studies included in the systematic review. Although not all of the original studies describe the location of the lesion within the tube, of those that did, 52 cases were located within the fimbriated end of the fallopian tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if you take biopsies from all recommended sites (paracolic gutters left and right, ovarian fossa left and right, pouch of Douglas and the peritoneal fold of the prevesical pouch), it will still be less than 1 % of the peritoneum [8]. Furthermore, Piedimonte et al [23] mentioned recent data in colorectal cancer indicating seeding of metastases through disseminated cancer cells while the carcinoma is still undetectable (less than 0.01 m 3 ). Therefore, as shown in our study, the routine sampling of peritoneal biopsies during RRSO does not appear to provide any additional information or additional oncological benefit.…”
Section: Discussionmentioning
confidence: 99%